2017
DOI: 10.1038/s41598-017-04823-1
|View full text |Cite
|
Sign up to set email alerts
|

Fam64a is a novel cell cycle promoter of hypoxic fetal cardiomyocytes in mice

Abstract: Fetal cardiomyocytes actively proliferate to form the primitive heart in utero in mammals, but they stop dividing shortly after birth. The identification of essential molecules maintaining this active cardiomyocyte proliferation is indispensable for potential adult heart regeneration. A recent study has shown that this proliferation depends on a low fetal oxygen condition before the onset of breathing at birth. We have established an isolation protocol for mouse fetal cardiomyocytes, performed under strict low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 26 publications
2
36
0
1
Order By: Relevance
“…The fusion protein CALM/AF10, t(10;11)(p13;q14), plays a crucial role in acute myeloid leukemia, acute lymphoblastic leukemia and malignant lymphoma [ 41 , 42 ]. Previous studies demonstrated that FAM64A contributes to cell cycle progression [ 43 , 44 , 45 ]. Overexpression of FAM64A was reported in leukemia, lymphoma and several types of solid cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fusion protein CALM/AF10, t(10;11)(p13;q14), plays a crucial role in acute myeloid leukemia, acute lymphoblastic leukemia and malignant lymphoma [ 41 , 42 ]. Previous studies demonstrated that FAM64A contributes to cell cycle progression [ 43 , 44 , 45 ]. Overexpression of FAM64A was reported in leukemia, lymphoma and several types of solid cancer [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that FAM64A, also named as CATS and PIMREG, participates in malignant transformation [10][11][12][13]. FAM64A was first studied in hematologic carcinomas, which was known as CALM/AF10 interacting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…levels strongly correlate with cell proliferation in both malignant and normal cells (18). FAM64A is a multifunctional protein that is involved in regulation of cell cycle progression, subcellular localization of the leukemogenic fusion protein CALM/AF10, and tumorigenesis (18)(19)(20)(21)(22). In a screen for proteins that regulate STAT3 activity, we identified FAM64A as a positive regulator of STAT3, which modulates binding of STAT3 to the promoters of its target genes.…”
Section: Significancementioning
confidence: 99%